P587 Association between vaginal bacteria and HIV acquisition risk among african women participating in the VOICE study. (14th July 2019) - Srinivasan, Sujatha; Richardson, Barbra; Wallis, Jacqueline; Fiedler, Tina; Hoffman, Noah; Proll, Sean; Chirenje, Z; Livant, Edward; Fredricks, David; Hillier, Sharon; Marrazzo, Jeanne
Abstract : Background: We previously identified seven vaginal bacteria associated with increased HIV acquisition risk among African women using taxon-directed quantitative PCR (qPCR). We sought to extend the search for high-risk bacteria using a sequential PCR approach. Methods: African women participating in a randomized placebo-controlled trial of daily oral vs. vaginal tenofovir-based pre-exposure prophylaxis for HIV (VOICE study) provided vaginal samples. Cases (177 HIV pre-seroconversion visits from 150 women who acquired HIV) and controls (531 visits from 436 women who remained HIV uninfected) were matched by study arm and site. The vaginal microbiota was characterized using 16S rRNA gene PCR and sequencing to assess associations between relative abundances of bacteria and HIV risk; bacterial taxa were ranked in descending order by score statistic using logistic models run on each taxon until a p-value=0.1. Taxa prevalent at ≥5% were selected for measurement of concentrations by qPCR. Relationship between bacterial concentrations and HIV risk was analyzed using Generalized Estimating Equation models, and adjusted for potential confounders. Results: Vaginal bacterial diversity among cases was higher than controls (p=0.0044). Analysis of relative abundance data identified 12 bacterial taxa associated with HIV risk that were not previously described. Six of these 12 taxa were selected for taxon-specific qPCR measurements. Concentrations of five of six taxa were significantly associated with increased risk for HIV acquisition. These include bacterial vaginosis-associated bacterium 2 (adjusted odds ratio (aOR)=1.57; 95% CI 0.97, 2.56), Candidate Division TM7 (aOR=2.04; 95% CI 1.14, 3.65), Prevotella amnii (aOR=1.53, 95% CI 0.95, 2.46), Porphyromonas Type 1 (aOR=2.04, 95% CI 1.27, 3.28), and Peptinophilus lacrimalis (aOR=1.55, 95% CI 0.98, 2.44). Dialister micraerophilus was not associated with HIV risk. Conclusion: A sequential PCR approach facilitated the identification of new bacteria associated with increased HIV acquisition risk. Interventions to decrease high-risk bacteria could be explored as one approach to reduce HIV risk in women. Disclosure: No significant relationships.